Student Photographers Using a Special Vehicle for Photographing Events
Student photographers for Cal Poly's newspaper, El Mustang, and campus yearbook, El Rodeo, used a special vehicle for photographing events, Cas Szukalski (seated in jeep, holding camera) took the action rodeo photo on this page.